Water Use in Mountain Areas: A Case of Modi Khola Watershed, Nepal - Rijal, Shiba Prasad (The Third Pole: Journal of Geography Education, 2009)
DOI: http://dx.doi.org/10.3126/ttp.v3i0.1779 The Third Pole Vol.3&4 2004 p.56-74